Assistance to the Baiturrahman Mosque Prosperity Council and Miftahul Ulum in Qibla Measurement - Surahman, Maman; Hamdani, Fahmi Fatwa Rosyadi Satria (Universitas Negeri Medan, 2023)
The mosque building, which is in the alley, sometimes escapes the monitoring of the accuracy of the Qibla direction. The difficulty of getting the sun's shadow directly into the mosque is one of the factors so that the instrument used to measure the Qibla only uses makeshift tools or only follows the location of the land used for the building. Such as Baiturrahman and Miftahul Ulum mosques in the Tamansari Village, with the position of building in an alley. The purpose of this PKM activity is to assist the Mosque Prosperity Council (DKM) in verifying the Qibla direction of their mosque so that Muslims can pray towards the Qibla with the help of an accurate tool. This mentoring activity uses a participatory action research approach so that DKM can utilize the sun qibla and mizwandroid instruments in aligning the Qibla direction of the mosque. The results of the mentoring activities at the Baiturrahman Mosque and Miftahul Ulum Mosque, namely the correction of the prayer rows conducted by the DKM of the mosque and the service team, where the difference in Qibla direction deviation is 8 degrees and 5 degrees, respectively. In addition, DKM and the service team have made corrections to the prayers’ rows at the imam's place and the first row in each mosque by attaching Qibla direction stickers as a benchmark for the direction of the rows.